Recent Advances in Mechanisms of Fracture and Fatigue (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on basic and applied research on fatigue and fracture processes in engineering of materials and composites. Special attention is given to understanding fracture processes from the point of view of micro and nano damage mechanisms related to material microstructure. Advanced experimental methods such as tomography, digital image correlation, high resolution electron microscopy and fractography are applied in combination with theoretical multiscale models based on finite element methods and fracture mechanics to reveal the fundamental causes of material failure.